2019
DOI: 10.21608/svuijas.2019.67087
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary doum supplementation on- productive and reproductive performance of male rabbits in Upper Egypt

Abstract: The objective of this work was conducted to study the effect of Doum (Hyphaenethebaica) supplementation on productive and reproductive performance of rabbit bucks in Upper Egypt during spring season. Thirty-two males16 California (CAL) and 16 Newzland (NEZ) rabbits 8 months old with average initial body weight 3.409±0.05 kg were randomly divided into four groups of 4 bucks each/breed (CAL and NEZ). Group 1 served as control fed a basal diet. Groups 2, 3 and 4 fed basal diets supplemented with 0.3, 0.6 and 0.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…California does showed recorded significant higher conception rate, kindling rate, litter size at birth and at weaning and lower mortality rate compared to the NEZ breed. These results are in agreement with (Hassanien et al, 2019;Fawaz et al, 2019a, b;Abdel-Wareth et al, 2019a, b;Bozkurt et al, 2014;Hippenstiel et al, 2011). Zeidan et.,al (2001) Similarly, Kindling rate, Litter size at birth and at weaning in CAL were significantly better than NZW rabbits .The study showed that the different levels of doum fed to rabbit does had nosignificant effect (P>0.05) on body weight at mating, kindling and weaning.…”
Section: Reproductive Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…California does showed recorded significant higher conception rate, kindling rate, litter size at birth and at weaning and lower mortality rate compared to the NEZ breed. These results are in agreement with (Hassanien et al, 2019;Fawaz et al, 2019a, b;Abdel-Wareth et al, 2019a, b;Bozkurt et al, 2014;Hippenstiel et al, 2011). Zeidan et.,al (2001) Similarly, Kindling rate, Litter size at birth and at weaning in CAL were significantly better than NZW rabbits .The study showed that the different levels of doum fed to rabbit does had nosignificant effect (P>0.05) on body weight at mating, kindling and weaning.…”
Section: Reproductive Performancesupporting
confidence: 87%
“…Keeping the merits of doum into view. Our previous research indicated physiological response of Doum on rabbits (Hassanien et al, 2019). The present study was conducted on the effect of dietary doum supplementation on productive and reproductive performance of does rabbits in Upper Egypt.…”
Section: Introductionmentioning
confidence: 92%